The Role Of The Principal As A Supervisor In Improving The Quality Of Elementary School Education - Hidayati, Ani Dwi Nazilah; Yuliejantiningsih, Yovitha; Haryati, Titik (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This study aims to examine the implementation of principal supervisory roles in improving educational quality. specifically analyzing the planning, implementation, and follow-up functions of supervision and their impact on educational quality enhancement. The research was conducted at SDN Kebondalem 01, Semarang Regency, which was selected due to its consistent educational quality improvement, evidenced by three consecutive years of BOSP Performance awards and significant score increases in national education reports. A qualitative descriptive case study approach was employed, involving in-depth interviews with three key informants (principal, teacher, and educational staff), non-participant observations, and document analysis. Data were analyzed using Miles and Huberman's model with triangulation techniques to ensure validity. The findings reveal that effective principal supervision operates through three interconnected functions creating sustainable educational quality improvement. The planning function demonstrates systematic data-driven approaches based on education report analysis and differentiated technique selection. The implementation function integrates traditional supervision methods with digital platforms (Performance Management and E-Kinerja), employing complete supervision cycles and collaborative approaches. The follow-up function emphasizes structured reflection and strategic planning ensuring supervision continuity. Measurable impacts show significant improvements: literacy scores increased from 90 to 100, numeracy from 66.67 to 90, character development from 60.54 to 72.67, and school achievements rose from 15 to 40 across various levels over three years Theoretically, this study contributes to educational leadership literature by demonstrating how digital integration enhances traditional supervision practices in elementary school contexts. Practically, the findings provide a replicable supervision model for principals and policymakers to improve educational quality through systematic, collaborative, and technology-enhanced supervision approaches.